(untitled) (International journal of artificial intelligence, 2026)
This article explores artificial intelligence (AI) as a complex scientific and socio-technological phenomenon, focusing on its theoretical foundations, historical development stages, and its growing role in shaping contemporary society. The study examines the transition from symbolic AI to machine learning and generative models, highlighting the interdisciplinary nature of the field. It also analyzes the interaction between AI technologies and social structures, including ethical challenges, economic transformation, and sustainability concerns. The paper argues that AI is not merely a technological advancement but a transformative force influencing human cognition, social relations, and global development trajectories.